Exploration of Domains and Elements of Integrated Training Competency Model through Work-Based Learning (WBL) - Ciptono, Argo; Abd Samad, Noorazman; Hassan, Razali; S, Muslim; Ismail, Affero (Journal of Technical Education and Training, 2021)
The exploration in this study is referred to the Integrated Training Competency Model through Work-Based Learning (WBL). This exploratory study utilized structured interview instruments that have been developed by the researcher. This research involved 7 respondents consisting of 4 automotive practitioners and 3 academicians in the automotive field to explore and determine domains and elements. The findings of the study show the percentage of agreement among the 7 experts. Domains and elements of Integrated Training Competence (ITC) through Work-Based Learning (WBL) were investigated in this study. It is found that there are three (3) main domains for the model namely: (1) Management / manager performance; (2) Cultural and (3) WBL learning quality. Meanwhile, for the quality of learning outcomes, there are four (4) main domains namely: (1) Mastery of Speed; (2) Student’s Professional Attitude; (3) Mental Readiness for Work, and (4) Freedom Independence. These findings used single round semi structured interview based on the Fuzzy Delphi Method (FDM) technical approach. The results of this exploration will be used to develop an Integrated Training Competency model through Work-Based Learning (WBL).